Impact of, Human Capital, Economic Factors, Energy Consumption, and Urban Growth on Environmental Sustainability in Morocco: An ARDL Approach - Asli, Hamdi El; Hamid, Lakhmaiss; Zineb, Afif; Mohamed, Azeroual (International Journal of Energy Economics and Policy, 2024)
This study aims to examine the impact of human capital, energy consumption, urbanization, growth, trade openness and foreign direct investment on Morocco’s environmental sustainability using annual data from 1970 to 2019 and, in light of, recommend policy implications. We used the ARDL approach to identify the potential linkage between carbon emissions and the explicative variables. The ADF unit root test is used to check the stationarity of all variables, showed that five of them become stationary after first differentiation. The result from the bound test indicated the existence of a long run relationship which confirmed the existence of co-integration with high speed of adjustment towards the long-run equilibrium. We found that increase in human capital leads to decrease in carbon emissions, meanwhile increase in both economic growth and energy consumption generate an opposite result, other things equal. Our finding validates the theoretical frame work involved in this study (STIRPAT: Stochastic Impact by Regression on Population, Affluence, and Technology, 1997) that confirms the possibility of promoting environmental sustainability through reducing carbon emissions, rationalizing energy consumption, reorienting economic growth into an eco-friendly model, building and enhancing human capital through education, besides working on rising economic openness and investment attractiveness of Morocco.